Emotional Expression in Children With ASD: A Pre-Study on a Two-Group Pre-Post-Test Design Comparing Robot-Based and Computer-Based Training - Lecciso, Flavia; Levante, Annalisa; Fabio, Rosa Angela; Caprì, Tindara; Leo, Marco; Carcagnì, Pierluigi; Distante, Cosimo; Mazzeo, Pier Luigi; Spagnolo, Paolo; Petrocchi, Serena (Frontiers in Psychology, 2021)
Studies found a delay in the development of facial emotion recognition and expression in children with an Autism. Several interventions have been designed to help children to fill this gap. The majority of them adopt technological devices (i.e., robots, computers, and avatars) as social mediators and reported evidence of improvement. Few interventions aimed at promoting emotion recognition and expression abilities and, among these, the majority focused on emotion recognition. One crucial point is the generalization of the ability acquired during the treatment to the naturalistic interactions. The present study aimed at evaluating the effectiveness of two technological-based interventions focused on the expression of basic emotions comparing a robot- to a “hybrid” computer-based training. Furthermore, we explored the engagement of the hybrid technological device introduced in the study as an intermediate step to facilitate the generalization of the acquired competencies in naturalistic settings. A two-group pre-post-test design was applied to a sample of 12 children (M = 9.33; ds = 2.19) with autism. Children were included in one of the two groups: group 1 received a robot-based training (n = 6); group 2 a computer-based training (n = 6). Pre- and post-intervention evaluation (i.e., time) of facial expression and production of four basic emotions were administered. Non parametric Anovas found significant time effects between pre- and post-intervention on the ability to recognize sadness [t(1)=7.35, p=.006; pre:M(ds)=4.58(.51);post:M(ds)=5], and to express happiness [t(1)=5.72, p=.016; pre:M(ds)=3.25(1.81); post:M(ds)= 4.25(1.76)] and sadness [t(1) = 10.89, p< .000; pre:M(ds)=1.5(1.32);post:M(ds)=3.42(1.78)]. The group*time interactions were significant for fear [t(1)=1.019, p=.03] and anger expression [t(1)=1.039, p=.030]. However, the Mann Whitney comparisons did not show significant differences between robot-based and computer-based training. No difference was found in the levels of engagement comparing the two groups, in terms of the number of voice prompts given during the interventions. Albeit the results are preliminary and they should be interpret with caution, this study suggests that two technology-based trainings perform similarly in promoting facial recognition and expression of basic emotions in children with an ASC. The findings represent the first step to generalize the abilities acquired in a laboratory trained situation to naturalistic interactions.